2016
DOI: 10.1155/2016/2165462
|View full text |Cite
|
Sign up to set email alerts
|

Mesenchymal Stem Cells Loaded with p5, Derived from CDK5 Activator p35, Inhibit Calcium‐Induced CDK5 Activation in Endothelial Cells

Abstract: The potential use of stem cells as therapeutics in disease has gained momentum over the last few years and recently phase-I clinical trials have shown favourable results in treatment of a small cohort of acute stroke patients. Similarly, they have been used in preclinical models drug-loaded for the effective treatment of solid tumours. Here we have characterized uptake and release of a novel p5-cyclin-dependent kinase 5 (CDK5) inhibitory peptide by mesenchymal stem cells and showed release levels capable of bl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 26 publications
1
2
0
Order By: Relevance
“…Previous work has identified that p5 offers protection to both neurons and endothelial cells [12,20]. Indeed, this present study has demonstrated a specific protection towards neurons in vitro.…”
Section: Discussionsupporting
confidence: 67%
See 2 more Smart Citations
“…Previous work has identified that p5 offers protection to both neurons and endothelial cells [12,20]. Indeed, this present study has demonstrated a specific protection towards neurons in vitro.…”
Section: Discussionsupporting
confidence: 67%
“…Human adipose-derived mesenchymal stem cells (hADMSCs) were provided by Professor Giulio Alessandri and Professor Valentina Ceserani. hADMSCs were isolated from peri-umbilical fat tissue and characterized as described [20]. Human neuroblastoma neuroblastic type SH-SY5Y cells and bovine aortic endothelial cells (BAECs) were cultured in Dulbecco's modified Eagle's medium (DMEM; Lonza) supplemented with 10% FBS and 1% L-glutamine.…”
Section: Cell Culturementioning
confidence: 99%
See 1 more Smart Citation